Performance Improvement of Standalone Solar PV Pumping System Using Supercapacitor - Kazi Kutubuddin Sayyad Liyakat (International Journal of Electrical Power and Machine Systems, 2026)
Two of the most pressing issues when it comes to rural communities of arid and semi-arid regions are water shortage and unstable grid electricity. Standalone solar photovoltaic (PV) pumping systems have been introduced as a clean, low maintenance alternative to diesel powered pumps, but their performance is limited by intermittent nature of sunlight and limited energy buffering capacity of conventional batteries. The paper is an investigation into the incorporation of high power, high energy density super capacitor bank as a hybrid storage component in a 5 -kW PV driven water pumping system. Detailed Modeling Framework is developed in MATLAB/Simulink that integrates a detailed PV array model, and MPPT controller. In key findings, it is demonstrated that the supercapacitor module mitigates the short duration power dips, caused by clouds, in delivering an average pump flow increase of 22 % and depth of discharge cycle reductions of 17. Also a results demonstrates that, average pump flow in Sunny days is 99%, in cloudy days is 88% and in partially cloudy days is 83% of its rated flow. The findings support the assumption that, given a well-planned layout of the conventional batteries, supercapacitors can contribute significantly to the reliability, efficiency, and economic feasibility of off grid solar water pumping systems.
Keywords: PV pump; Pump power; Pumping System; Supercapacitor; Water output; battery